‘It is empowering…’ Teachers’ voices on action research using Flanders' Interactional Analysis Categories (FIAC) for peer observation to improve teaching and learning of English language - Dzakiria, Hisham; Mohamed, Abdul Halim; Hisham, Badrul; Malek, Zahril Anwar; Said, Shahrul Niza (Faculty of Communication and Modern Languages, Universiti Utara Malaysia, 2007)
Observing teachers especially experienced teachers can be a difficult task. Nevertheless, observation is an effective means to evaluate the effectiveness of teaching and learning practice of any course or programme. Peer observation is one of the effective ways with relative ease. This paper discusses the findings of a study that involves three ESL (English as a Second Language) teachers at Changlon Secondary School in Kedah Malaysia. This study incorporates the use of Flanders' Interactional Analysis Category (FIAC) for Teacher Support Team (TST) programme between Universiti Utara Malaysia(UUM) and the school. The paper begins first by explaining the involvement of the teachers and their feelings about peer observation. This paper then highlights teachers’ feelings and perceptions towards FIAC as an alternative tool to observe and improve teaching effectiveness and how its use create an awareness of the kind of teaching that takes place in their classrooms. The dogma of learner-centred versus teacher-centred teaching was evidently discussed. The paper concludes by providing ways to make the classrooms more learner-centred as opposed to the current practice of the teachers which are more teacher-centred.